An Assessment of the Educational Service Quality Rendered: A Stakeholder’s Perception - Calvez, Keen Jolliheart; Mercado, Matias Jr.; Jovero, Neilgene; Lespasana, Cristy; Ligan, Riza Jean; Perez, Jhezélane Grace (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluates the educational service quality of Holy Cross of Mintal, Inc. (HCMI) by examining stakeholder perceptions and institutional performance. Anchored on the SERVQUAL model (Parasuraman, Zeithaml, & Berry, 1988) and the SERVPERF model (Cronin & Taylor, 1994), the study adopts a descriptive-quantitative design with a predictive-discriminant approach. Data were collected from 200 stakeholders, including students, parents, alumni, and employees, using a 44-item questionnaire adapted from Baniya (2016) and measured through a five-point Likert scale. Descriptive statistics and discriminant analysis were employed to determine service quality levels and identify variables that distinguish the highest perception group. Findings reveal an overall “High” level of service quality (M = 3.86), with Assurance emerging as the strongest dimension, while Tangibles recorded the lowest score. The distribution of responses indicates that 75.5% of stakeholders fall within high and very high satisfaction levels. Discriminant analysis identified Reliability, Responsiveness, and Empathy as the key predictors of the “Very High” perception group, with Reliability as the most significant determinant. These results indicate that consistent service delivery and human-centered engagement are critical in achieving higher stakeholder satisfaction. The study concludes that while HCMI demonstrates strong institutional performance driven by human capital, improvements in infrastructure and technological resources are necessary. It recommends strengthening operational reliability, enhancing responsiveness and empathy, and investing in ICT and facilities to elevate stakeholder satisfaction. The findings align with Sustainable Development Goals such as SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation and Infrastructure). The study contributes to educational, institutional, and technological sustainability by promoting data-driven service improvement, strengthening stakeholder trust, and supporting continuous quality enhancement in educational institutions.
Keywords: Educational service quality; Empathy; Reliability; Responsiveness; SERVPERF model; SERVQUAL model; Stakeholder perception; Tangibles